ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH PENDUDUK MISKIN - Jayaningtyas, Lailatul; Bintoro, Nugroho Suryo (Journal of Development Economic and Social Studies, 2023)
Poverty is a problem where no country or region can be free from the threat of poverty. Likewise with Indonesia, of the 34 provinces in which East Java Province is an area that has the largest number of poor people compared to other provinces. Based on the principles of regional autonomy and Keynesian theory, the government's efforts to reduce the number of poor people can be through allocating education expenditures and health expenditures. In this regard, there are several other factors that can affect the level of poverty, including per capita income, population growth and unemployment. Therefore, these five variables will be tested to determine their effect on the number of poor people in East Java. Using the multiple linear regression analysis method with panel data, data will be taken from 38 regencies/cities in East Java Province in 2010-2020. Where this study shows that education expenditures, health expenditures, per capita income, and population growth on the number of poor people have a significant influence. While unemployment has no significant effect on the number of poor people. Thus, the local government can make a series of policies that can overcome the problem of high poverty rates in East Java through these 4 significant variables.